Ethnic Conflict in Nigeria: A Need for True Federalism - Wani, Hilal Ahmad; Suwirta, Andi (TAWARIKH, 2013)
ABSTRACT: Nigeria is one of the major democracies in African continent. It is a multi-cultural and multi-ethnic society. There are different identities and segments in this society. To call it a diversified society would not be wrong, a society with different religions, cultures, and languages. Ethnicity is generally regarded as the most basic and politically salient identity in Nigeria. This paper is a new attempt to relook the significance and relevance of true federalism in Nigeria. To examine how far the State machinery and political institutions had been successful in accommodating different interests of various identities. Major democracies are based on the rule of law and protection of human rights that should be taken into consideration at the first level. Only true federalism and decentralization is a way forward to create balance and accommodation among different identities in Nigerian society. Nigeria needs good institution which could be successful in maintaining good governance. Therefore, dysfunctional political system reform and restructuring for maintaining social justice with all without any discrimination. A true federalism and true democracy can be used as a real panacea of ethnic conflict. In summation, it can be said that shaping and sharing of powers could be also better option for creating a peaceful and prosperous in Nigeria.KEY WORDS: Ethnic conflict, federalism, true democracy, decentralization, national integration, and peaceful and prosperous in Nigeria.Â Â About the Authors: Dr. Hilal Ahmad Wani is a Research Fellow at the Centre for Civilizational Dialogue UM (University of Malaya), Kuala Lumpur, Malaysia; and Andi Suwirta, M.Hum. is a Senior Lecturer at the Faculty of Social Studies Education UPI (Indonesia University of Education) in Bandung, Indonesia. The authors can be contacted via their a-mail at: wanihilal@gmail.com and atriwusidna@gmail.comHow to cite this article? Wani, Hilal Ahmad & Andi Suwirta. (2013). âEthnic Conflict in Nigeria: A Need for True Federalismâ in TAWARIKH: International Journal for Historical Studies, Vol.5(1) October, pp.57-70. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia] and UVRI [Universitas Veteran Republik Indonesia], ISSN 2085-0980.Chronicle of the article: Accepted (August 17, 2013); Revised (September 20, 2013); and Published (October 28, 2013). Â